Some Evidence on the Nature of Relearning Curves. - Bailey, Charles D.; McIntyre, Edward V. (The Accounting Review, 1992)
Presents the findings of the study designed to provide evidence on the nature of relearning curves. Study design; Functional forms of learning and relearning curve equations; Application of relearning curve equations to data; Relationship between forgetting and model choice; Tests of predictive ability.